If Docker is the Answer, What is the Question? - Zhu, Hong; Bayley, Ian (2018 IEEE Symposium on Service-Oriented System Engineering (SOSE), 2018)
The recent rise of cloud computing poses serious challenges for software engineering because it adds complexity not only to the platform and infrastructure, but to the software too. The demands on system scalability, performance and reliability are ever increasing. Industry solutions with widespread adoption include the microservices architecture, the container technology and the DevOps methodology. These approaches have changed software engineering practice in such a profound way that we argue that it is becoming a paradigm shift. In this paper, we examine the current support of programming languages for the key concepts behind the change in software engineering practice and argue that a novel programming language is required to support the new paradigm. We report a new programming language CAOPLE and its associated Integrated DevOps Environment CIDE and demonstrate the utility of both.